Fast and slow light generation using chaotic signals in nonlinear microring resonators for communication security - Pornsuwancharoen, Nithiroth; Chalyasoonthorn, Sawatsakorn; Yupapin, Preecha P. (My University, 2009)
We propose a new system of signal security using nonlinear micro ring resonators for optical communication system. When a soliton pulse Is input into the system, the chaotic signal Is generated and multiplexed into the optical link. The chaotic waveform can be canceled using an add/drop device connected into the transmission link. Using the appropriate ring parameters, the original signal can be retrieved. An other application results from the fact that the fast and slow light behaviors can be presented, and can be seen using the add/drop multiplexers. In some cases, we can generate signal to obtain the two identical "signal" and "ghost" signals, which are observed in a different time frame. In this application, communication security can be performed when the required information is multiplexed and performs the link using the chaotic signal, fast and slow light, and signal and ghost signals, where the original signal can be retrieved by the known clients. © 2009 Society of Photo-Optical Instrumentation Engineers.
Keywords: Communication security; Fast and slow lights; Ghost and signal generation; Optical communication